Social exposure to an antiretroviral treatment programme in rural KwaZulu-Natal - Bor, Jacob; Bärnighausen, Till; Newell, Colin; Tanser, Frank; Newell, Marie-Louise (Tropical medicine & international health, 2011)
Objective: To investigate the prevalence of social exposure to a large, government-run ART programme in rural South Africa. Method  Clinical data on 6681 patients were matched with demographic data on a nearly complete cohort of 102 359 people residing in the programme catchment area. We calculated the proportion of residents in the demographic surveillance area that were members of a household, or resided in a compound where someone had initiated ART or received pre-ART care. Results  By January 2010, 3% of the population had initiated ART. However, 25% of the population shared household membership or resided in a compound with someone who had initiated ART; 40% shared household or living arrangements with people who had either initiated ART or were enrolled in pre-ART care. Conclusion  Such high rates of social exposure suggest that ART programmes in HIV endemic areas are likely to have significant population-level effects on social norms and economic welfare. These results also point to the opportunity to reach large numbers of people with health and social services through existing ART programmes